Comparative analysis of sustainable manufacturing process in the use of polycarbonate compared to the use of aluminum in mobile phone back covers - Syed Mubarak Subukutheen (2014)
The world has an estimated population of 7 billion people, out of which 5 billion people are connected through the means of mobile telephony. Compared to 1991, when the number of mobile phone users amounted to only 16 million, in the year 2002, the numbers exceeded 1 billion. The expected number of users by the year 2017 is expected to be an approximate 5 billion users. Mobile phones in the last ten years have become an integral part of the business culture. The rising demand for mobile phones for personal and work related uses have created a heavy demand for these hand held devices. They are used for sending instant messages, socializing, paying bills and even electronic banking. The total number of phones shipped in the year 2013 was tallied to be 1.8 billion pieces in total. As part of corporate responsibility and commitment to eco-efficient practices, major companies such as Nokia, Samsung, LG and others are expected to reduce wastage and introduce sustainable manufacturing practices. The initiative must be emphasized to be in place to have means to recover the materials used in these phones at the end of the life of the device. This study aims to assess the environmental benefits of using polycarbonate compared to aluminium for the back cover of mobile phones and propose the usage of one material over the other when virgin raw material is used. This study has taken reference from the various white papers, international guidelines, and studies by internationally recognized organizations such as IES (Institution of Engineers, Singapore), UL (United Laboratories) and standards regulated by EU (European Union) RoHS (Regulations of Hazardous Substances). In this analysis, 3D models of existing smartphone models were designed, analysed and studied in detail. This report has analysed and compared between two commonly used materials, aluminium and polycarbonate. The focus was placed on calculating the energy, carbon footprint, water consumption and cost of raw material during the first life of the material as well as the energy and carbon footprint for the second life. This is to formulate a better model based on sustainable manufacturing practices that is recommended to HTC, an international mobile phone maker for their next flagship model, the HTC 2. The detailed energy and carbon footprint report was tabulated based on ECO-Granta energy analysis software. Some key findings showed that, polycarbonate in its first life required only 26% of energy expansion and 24.5% carbon footprint contribution compared to aluminium. In the second life, the usage of aluminium required 13% lesser energy compared to polycarbonate. Upon concluding the differences between the two materials, this study further proposes to consider the use of polycarbonate material on all mobile phones made by top manufacturers of mobile phones when virgin raw material is used, to achieve a sustainable model by reducing energy consumptions and carbon footprint. Aluminium can be considered if material used is in its second life.